Kjønn og rett Kvinne-, kjønns- og likestillingsperspektiver i jusstudiet - Ikdahl, Ingunn; Hellum, Anne; Asland, John; Bruserud, Herman; Astrup Hjort, Maria; Gudmundsdottir Jonassen, Bjørk; Skilbrei, May-Len (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2022)
Women's law, gender equality and non-discrimination law have constituted fields of research at the Faculty of Law at the University of Oslo for decades. Law establishes rights and obligations, legal protections and punishments - it can create, maintain and transform society's distribution of power and resources between individuals and groups. It is thus an important part of legal education to create understanding of how legal constructs, rules and decisions can lead to - or counteract - inequality and discrimination. This book presents various types of gender perspectives in a range of disciplines within law. The chapters cover areas within both public and private law, such as family law, administrative law, welfare law, contract law, corporate law, and criminal law. The book also includes gender perspectives in such related disciplines as legal philosophy, legal sociology, criminology, law and economics, and professional ethics for lawyers. Gender and Law: Women's, Gender and Gender-Equality Perspectives in Legal Studies has been written primarily with law students in mind, but everyone with an interest in the relationship between law, gender, society and politics will find it relevant.